Perancangan Tata Letak Fasilitas Kaos V-Neck untuk Peningkatan Daya Saing - Prillia Haliawan; Febrisi Dwita; Dwiwahjuni Wulandari (Penerbit Goodwood, 2024)
Purpose: The purpose of this study was to address the numerous complaints received by PTRT management concerning the production process of V-Neck t-shirts in six divisions during 2023. The goal was to redesign the layout, particularly the process-oriented layout, to improve the efficiency and reduce operational costs.Methodology: The management employed a quantitative approach to redesign the layout. The analysis involved calculating and comparing the total number of movements in the production process before and after the redesign. The methodology focused on reducing the number of movements required to enhance the efficiency.Results: The redesigned layout resulted in a reduction of 300 movements per week, equating to a 1.8% decrease from the initial total of 16,800 to 16,500 movements. This reduction also led to a corresponding decrease in the cost of movement, thereby reducing Rp. Three hundred per week, a 1.8% reduction in costs.Conclusions: The new design obtained fewer movements, namely 300 movements per week or 1.8% lower compared to the initial total movements.Limitations: The study is limited by the scope of data, which is specific to the production of V-Neck t-shirts in 2023 within the six divisions. The results may not be generalizable to other products or time periods, and the analysis focused solely on movement efficiency without considering other potential factors, such as employee productivity or material flow.Contribution: The redesign of the layout contributes to the overall competitiveness of PTRT management by streamlining the production process, reducing costs, and potentially minimizing complaints related to the production of V-neck t-shirts. This process-oriented approach to layout design can serve as a model for future improvement in other production areas.